Perancangan Buku Ilustrasi ‘Belajar Jajanan Tradisional’ Sebagai Media Edukasi Berbasis Kearifan Lokal Bagi Siswa SDN 1 Tanggungharjo - Panca Ardhi Noer Cahaya; Irdha Yunianto; Ayyub Hamdanu Budi Nurmana M. S (UNIVERSITAS STEKOM, 2026)
Local wisdom, particularly traditional snacks, constitutes an essential part of national cultural identity that needs to be introduced from an early age. However, observations at SDN 1 Tanggungharjo revealed that students' understanding of traditional snacks remains low, compounded by a lack of contextual and engaging visual learning media. This study aims to design an illustrated book titled